Perancangan dan Analisa Implementasi LTE Home pada Jaringan 4G LTE di Frekuensi 2300 Mhz - Asri Wulandari; Toto Supriyanto; Mohammad Itsnan (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Negeri Balikpapan, 2019)
Design and analysis of lte home implementation on 4g lte networks in 2300mhz frequency. The demand for data connections for customers is currently increasing. FTTx as one of the Fix broadband technology (FBB) has several weaknesses, especially when applied to rural areas. LTE Home as a smart home technology is a form of WTTx 4G LTE technology service that is expected to be able to meet the data needs of customers. This study aims to design and analyze the implementation of LTE home by measuring the value of QoS Class Identifier (QCI) and the value of Radio Frequency Key Performance Indicator (RF KPI) to improve network reliability for voice and data communication services. Some parameters measured are packet loss, delay, jitter, throughput for QCI values and Radio Signal Received Power (RSRP) and Radio Signal Received Quality (RSRQ) for RF KPI values.The results of RF KPI Measurement show that the value for RSRP is -89dBm. This value is quite good because it matches the predetermined KPI standard, which is between -70 to -90 dBm. For RSRQ values obtained for -11dBM, this result is classified as good according to the KPI standard which is <-8 dBm. These results indicate that the quality of 4GLTE network services provided for LTE Home implementation services has met RF KPI standard values. Whereas for the QCI parameters obtained results that both voice call and video streaming, the value still meets the standard Good for the User Experience KPI (QCI) value that is packet loss <5%, delay <150 ms and jitter <75 msKeywords: LTE home, RF KPI. QCI, RSRP, RSCP,packet loss, jitter